La comunicación y la información en gobiernos locales: Persistencia de prácticas difusionistas de comunicación en organizaciones gubernamentales del Valle del Cauca (Colombia) - López Rojas, Ana María (2016)
This article presents the results of a research on the communicative exercise in ten major's offices in Valle del Cauca, using a diagnosis methodology focused in the application of the Public, Informative, and Organizational Communication Model for State Entities, which includes elements from the Standard Internal Control Model. We assume public communication as the one that happens in the public scenario and, from the governmental level, favors citizen access, discussion, visibility, participation, and debate aimed at generating trust in the State. We found that, although broadcast communication practices persist in these entities, their perception and demand have changed. This can be seen in the differentiation made by public officials between communication and information, understanding the former as an internal need to improve the work environment, while the latter is a fundamental requirement to interact with citizens.